Optimizing the Creative Problem Solving Learning Model to Enhance Students’ Critical Thinking Skills - Fasyawalyra Putri Arvina; Muhammad Akmansyah; Era Octafiona (Hikmah, 2025)
The low level of critical thinking skills among students in Islamic Religious Education remains a serious problem, mainly due to the dominance of conventional teacher-centered learning methods. In response to this problem, this study examines the application of the Creative Problem Solving learning model in improving the critical thinking skills of students in Islamic Religious Education at SMP IT Cahaya Ilmu, Bandar Lampung. This study used a quasi-experimental design involving an experimental group and a control group. Data collection was conducted through pre-tests and post-tests, observations, and questionnaires. The results showed that the application of the Creative Problem Solving model significantly improved students' critical thinking skills, particularly in problem solving and the application of Islamic Religious Education concepts. In addition, Creative Problem Solving was also able to increase students' active involvement and deepen their understanding of Islamic values. The implications of this study emphasize the importance of integrating problem-solving-based learning models into the Islamic Religious Education curriculum as a strategic effort to respond to the demands of 21st-century learning and shape students who are critical, reflective, and have Islamic character.